2011
DOI: 10.1080/00038628.2011.613642
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between wall reflectance and daylight factor in real rooms

Abstract: To reduce lighting loads and meet targets set in building codes, architects are encouraged to make maximum use of highreflectance colours for internal surfaces. Although in theory improving daylight factors and reducing electricity consumption of lighting circuits, this can constrain choice and may conflict with aesthetic desires. In this article, we examine the relationship between changes in surface albedo and changes in daylight factor for typical non-domestic spaces. The issue is tackled using both an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The large window area and room height in the wood room, rather than the interior surfaces, explains this difference. This finding relates to the work of Simm and Coley (2011), who found that differences in wall surface finishes had less impact on the daylight factor than predicted.…”
Section: Quantitative Analysis -Indoor Environmental Conditionssupporting
confidence: 60%
“…The large window area and room height in the wood room, rather than the interior surfaces, explains this difference. This finding relates to the work of Simm and Coley (2011), who found that differences in wall surface finishes had less impact on the daylight factor than predicted.…”
Section: Quantitative Analysis -Indoor Environmental Conditionssupporting
confidence: 60%
“…It also applies radiosity techniques [15]. In order to validate this software in a research [42] the Relux software was compared with SPOT and DAYSIM software and it was found that the Relax calculation process is very fast while the SPOT and DAYSIM calculations are costly and time consuming and other Relux error rates are lower. In fact, according to Table 1, the lighting process and detail of Relux software [40] uses the Radiosity method and in some cases also uses the Ray tracing method.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain the amount of daylight indoors, the intensity of the outdoor lighting needs to be calculated to be aware of the amount of outdoor light received indoors. Exterior light can reach the building through window glass, skylights or other openings, in three ways [42].…”
Section: Daylight Factor (Df)mentioning
confidence: 99%
“…The project needs to judge the building lighting from multiple dimensions of illumination, so the following lighting parameters shown in Table 2 are adopted for the project: daylight factor [11] [12], illumination uniformity (U0) [12], daylight autonomy [13], and daylight glare probability [14].…”
Section: Study Parametersmentioning
confidence: 99%